An attenuated total reflection (ATR) and Raman spectroscopic investigation into the effects of chloroquine on Plasmodium falciparum-infected red blood cells. Issue 7 (5th February 2015) - Kozicki, M.; Creek, D. J.; Sexton, A.; Morahan, B. J.; Wesełucha-Birczyńska, A.; Wood, B. R.
Abstract : Attenuated Total Reflection Fourier Transform Infrared (ATR-FTIR) and Raman spectroscopy were used to compare chloroquine (CQ)-treated and untreated cultured Plasmodium falciparum -infected human red blood cells (iRBCs). Abstract : Attenuated Total Reflection Fourier Transform Infrared (ATR-FTIR) and Raman spectroscopy were used to compare chloroquine (CQ)-treated and untreated cultured Plasmodium falciparum -infected human red blood cells (iRBCs). The studies were carried out in parallel from the same starting cultures using both spectroscopic techniques, in duplicate. ATR FTIR spectra showed modifications in the heme vibrational bands as well as increases in the CH2 /CH3 stretching bands in the 3100–2800 cm −1 region of CQ-treated iRBCs consistent with an increase in lipid content. Other changes consisted of secondary structural variations including shifts in the amide I and II modes, along with changes in RNA and carbohydrate bands. Raman microspectroscopy of single red blood cells using 532 nm revealed subtle changes in the positions and intensity of ν 37 of the core size region marker band and ν 4 in the pyrrole ring-stretching region between untreated and CQ-treated iRBCs. Similar patterns in the corresponding relations were also observed in the non-fundamental (overtone region) between the control and treated cells. These differences were consistent with higher levels of oxygenated hemoglobin (oxyHb) in the treated cells as shown in a Principle Component Analysis (PCA) loadings plot. The results obtained demonstrate that vibrational spectroscopic techniques can provide insight into the effect of quinolines on iRBCs and thus may assist understanding the sensitivity and resistance of new and existing anti-malarial drugs.